2015
DOI: 10.1007/s10457-015-9817-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the causes of high biodiversity of Iberian dehesas: the importance of wood pastures and marginal habitats

Abstract: In extensive low input farming and in agroforestry systems, the importance for biodiversity of managed productive fields with respect to unmanaged marginal habitats that occupy a low proportion of farm surface, is still poorly understood, contrasting with the well-known key importance of marginal habitats in intensive systems. We analyzed the importance of open and wood pastures and marginal habitats for species richness of Iberian dehesas in Central-Western Spain. We sampled 155 plots classified into 9 genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 64 publications
(53 reference statements)
4
53
0
Order By: Relevance
“…Minirhizotrons are non-destructive measurements but require the presence of an observatory. Artefacts due to observatory presence are particularly acute close to the time of installation (Joslin et al, 2001) and there is little consensus towards an appropriate time to leave observatories before good data are collected (see Johnson et al, 2001;Mueller et al, 2018;Strand et al, 2018). Slow-growing species may also take considerably longer than this time to equilibrate (Strand et al, 2018) but most (perennial) Q. ilex roots probably reached deeper soil layers than our observations (Moreno et al, 2005), causing both of our methods to mostly sample herbaceous layer roots.…”
Section: Methodological Considerationsmentioning
confidence: 89%
See 1 more Smart Citation
“…Minirhizotrons are non-destructive measurements but require the presence of an observatory. Artefacts due to observatory presence are particularly acute close to the time of installation (Joslin et al, 2001) and there is little consensus towards an appropriate time to leave observatories before good data are collected (see Johnson et al, 2001;Mueller et al, 2018;Strand et al, 2018). Slow-growing species may also take considerably longer than this time to equilibrate (Strand et al, 2018) but most (perennial) Q. ilex roots probably reached deeper soil layers than our observations (Moreno et al, 2005), causing both of our methods to mostly sample herbaceous layer roots.…”
Section: Methodological Considerationsmentioning
confidence: 89%
“…While root biomass is a direct measure of root C stocks, it is also generally highly inconsistent in experimental responses (e.g. Arnone et al, 2000;Mueller et al, 2018). Other physical attributes (such as spatial distribution of root systems, or traits such as root length density, RLD) may be more relevant for explaining plant function and not just standing biomass as they relate to functional properties; for example as root diameter and density vary, RLD relates more directly than biomass to soil exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Migliavacca et al, [40] found that differences in LAD related to nutrient availability could explain strong differences in the optical properties of the grassland layer in the same study site of this article. Former works accounted for 145 different species throughout the year in the study area [44]. Such biodiversity makes unfeasible scaling through species-based metrics such as in [78], and makes valuable use of modeling approaches that can be validated at a proximal sensing scale to later produce remote estimates of vegetation properties, as in this work.…”
Section: Discussionmentioning
confidence: 99%
“…The grass layer covers almost the totality of the soil, even under the tree canopy, and combines different functional types: grasses, forbs, and legumes [40]. This layer is highly dynamic [41] and biodiverse in space and time, depending on the availability of resources [42][43][44]. Its strong temporal dynamics are characterized by two seasonal biomass peaks with a maximum in spring and a second maximum after the summer decay, following the soil re-wetting phase.…”
Section: Study Sitementioning
confidence: 99%
“…Most semi-natural grasslands in the area have some wooded cover, but with a large variation in terms of tree density, ranging from just a few to more than 200 trees/ha (Jakobsson & Lindborg, 2015). Wooded pastures like these are essential for biodiversity conservation (Dicks et al, 2014;Mosquera-Losada et al, 2012) due to management continuity and the complex habitat structure that generate high biodiversity values across taxa (Bugalho, Caldeira, Pereira, Aronson, & Pausas, 2011;Hartel & Plieninger, 2014;Moreno et al, 2016).…”
Section: Study Systemmentioning
confidence: 99%